The Effects of a Supervisor’s Active Intervention in Subordinates’ Judgments, Directional Goals, and Perceived Technical Knowledge Advantage on Audit Team Judgments - Peecher, Mark E.; Piercey, M. David; Rich, Jay S.; Tubbs, Richard M. (The Accounting Review, 2010)
ABSTRACT: Prior research shows that an audit supervisor’s active intervention in a subordinate’s judgment distorts that judgment. However, subordinates’ judgments are only one input into audit team judgments. How do supervisors finalize audit team judgments after actively intervening in their subordinates’ judgments? In an experiment using audit teams, supervisors with weaker or stronger goals to reach a client-preferred conclusion either were or were not asked to first actively coach a subordinate’s judgment (i.e., active intervention) before reviewing it and finalizing the audit team’s judgment. Supervisors’ intervention influenced subordinates’ inputs, which, in turn, supervisors incorporated into their final judgments. More interestingly, intervention biased supervisors’ final judgments, controlling for supervisor directional goal strength and for concurrent effects on subordinates’ inputs. However, supervisors distorted their judgments less as they perceived a larger technical knowledge advantage over subordinates. In a second experiment, auditors appear aware of the bias-reducing knowledge advantage effects but unaware of the bias-increasing active intervention effects. We discuss implications for audit team judgments and audit quality control.